Smart (phone) investing? A within investor-time analysis of new technologies and trading behavior - Ankit Kalda; Benjamin Loos; Alessandro Previtero; Andreas Hackethal (Leibniz Institute for Financial Research SAFE, 2021)
Using transaction-level data from two German banks, we study the effects of smartphones on investor behavior. Comparing trades by the same investor in the same month across different platforms, we find that smartphones increase purchasing of riskier and lottery-type assets and chasing past returns. After the adoption of smartphones, investors do not substitute trades across platforms and buy also riskier, lottery-type, and hot investments on other platforms. Using smartphones to trade specific assets or during specific hours contributes to explain our results. Digital nudges and the device screen size do not mechanically drive our results. Smartphone effects are not transitory
Keywords: 330; fintech; investor behavior; financial risk-taking; lottery-type assets; investment biases; trend chasing; spillover effects